Mixed housing with DBA/2 mice induces stress in C57BL/6 mice: implications for interventions based on social enrichment - Kulesskaya, Natalia; Karpova, Nina N.; Ma, Li; Tian, Li; Voikar, Vootele (Frontiers in Behavioral Neuroscience, 2014)
Several behavioral interventions, based on social enrichment and observational learning are applied in treatment of neuropsychiatric disorders. However, the mechanism of such modulatory effect and the safety of applied methods on individuals involved in social support need further investigation. We took advantage of known differences between inbred mouse strains to reveal the effect of social enrichment on behavior and neurobiology of animals with different behavioral phenotypes. C57BL/6 and DBA/2 female mice displaying multiple differences in cognitive, social and emotional behavior were group-housed either in same-strain or in mixed-strain conditions. Comprehensive behavioral phenotyping and analysis of expression of several plasticity- and stress-related genes were done to measure the reciprocal effects of social interaction between the strains. Contrary to our expectation, mixed housing did not change the behavior of DBA/2 mice. Nevertheless, the level of serum corticosterone and the expression of glucocorticoid receptor Nr3c1 in the brain were increased in mixed housed DBA/2 as compared with those of separately housed DBA/2 mice. In contrast, socially active C57BL/6 animals were more sensitive to the mixed housing, displaying several signs of stress: alterations in learning, social and anxiety-like behavior and anhedonia. These behavioral impairments were accompanied by the elevated serum corticosterone and the reduced expression of Nr3c1, as well as the elevated Bdnf levels in the cortex and hippocampus. Our results demonstrate the importance of social factors in modulation of both behavior and the underlying neurobiological mechanisms in stress response, and draw attention to the potential negative impact of social interventions for individuals involved in social support.